Analysis of Examination Results of Erythrocyte Index in Pulmonary TB Patients Labuang Baji General Hospital, Makassar City - Asni Hasanuddin; Rony Setianto; Belinda Arbitya Dewi (NSMRJ: Nusantara Scientific Medical Research Journal, 2022)
The high rate of transmission of tuberculosis (TB) in Makassar City is very concerning. Data from the Makassar Health Office (Dinkes) in 2019 there were 5,412 TB cases. The data then decreased during the pandemic to 3,260 cases in 2020. And 3,911 cases in 2021 with a recovery rate of 83% in 2019 and 85% in 2020. The purpose of this study was to determine the value of the erythrocyte index in patients with pulmonary tuberculosis at the Hospital of Labuang Baji, Makassar City. The type of research used is laboratory observation with descriptive method. The population in this study were all patients with pulmonary tuberculosis as many as 11 people with pulmonary tuberculosis. The results obtained are known for the MCV value, 8 tuberculosis patients have a normal MCV value, 2 patients have a low MCV value and one has a high MCV value, for the MCH value, 6 tuberculosis patients have a normal MCH value, 4 patients have a high MCH value. low and one patient had a high MCH value, for the MCHC value 4 people with tuberculosis had a normal MCHC value and 7 patients had a low MCHC value.